Potencial do turismo internacional de Cabo Verde - Conceição, Ilze Eneida Paris da (2014)
Over the years, international tourism has grown rapidly to the point of being considered the world's largest industry, with significant contributions to the economy and the development of small countries. Cape Verde is a small island state, composed of ten islands, specializing in the tourism industry, with strong emphasis on international tourist demand. Considering that international tourism has great share of gross domestic product and the service sector of Cape Verde, it is essential that the country continues to attract and retain tourists to support the development of the economy and the country. For this it is necessary to know what influences the international tourism demand in the country. Thus, the goal of research is to analyze the potential of the international tourism market of Cape Verde, highlighting the attractiveness of international demand and the analysis of the tourism competitiveness of the islands that make up the archipelago. It is an analytical research with quantitative approach, using data supplied by the National Statistical Institute of Cape Verde and the Central Bank of Cape Verde. The data were analyzed with the statistical software Eviews7® by means of an autoregressive econometric model. Still calculated preference index and saturation of the tourist islands of Cape Verde, as well as their market shares. The results showed that the international tourism demand for Cape Verde is influenced positively by the hotel industry, the last tourist flow and the exchange rate. The indices of tourist preference indicate that the islands of Sal and Boa Vista are the most attractive tourists in Cape Verde, but also feature tourist saturation problems, which may result in social and environmental damage. It is concluded that reflects Cape Verde tourist saturation problems, which shows the need for integrated planning and detailed to minimize social and environmental problems, as well as direct investments to crowded islands, innovating to make them attractive so that they can contribute for the development and formulation of strategies to promote sustainable tourism in the country.